1997
DOI: 10.1177/000348949710600813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indomethacin, Dexamethasone, and Erythromycin on Endotoxin-Induced Intraepithelial Mucus Production of Rat Nasal Epithelium

Abstract: We produced hypertrophic and metaplastic changes of goblet cells in rat nasal respiratory epithelium by the intranasal instillation of endotoxin (ETN). In the present study, we examined in vivo effects of indomethacin (IND), dexamethasone (DEX), and erythromycin (EM) on intraepithelial mucus production using this animal model. Intraperitoneal injection of IND (2 to 4 mg/kg body weight x 4 days) or DEX (4 to 8 mg/kg body weight x 4 days) significantly inhibited intraepithelial mucus production induced after 3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…These results indicate that neutrophil elastase is an important mediator of endotoxin-induced epithelial mucus production; however, other inflammatory mediators are also probably involved in this change. In a previous study, we showed that intraperitoneal injection of indomethacin (an inhibitor of the cyclooxygenase pathway) partially inhibits endotoxin-induced mucus production, 11 but that the cysteinyl LT (LTC4, LTD4, and LTE4) antagonist ONO-1078 did not effeet this change (data not shown). These findings suggest that prostaglandins, but not cysteinyl LTs, mediate endotoxin-induced mucus production.…”
Section: Discussionmentioning
confidence: 90%
“…These results indicate that neutrophil elastase is an important mediator of endotoxin-induced epithelial mucus production; however, other inflammatory mediators are also probably involved in this change. In a previous study, we showed that intraperitoneal injection of indomethacin (an inhibitor of the cyclooxygenase pathway) partially inhibits endotoxin-induced mucus production, 11 but that the cysteinyl LT (LTC4, LTD4, and LTE4) antagonist ONO-1078 did not effeet this change (data not shown). These findings suggest that prostaglandins, but not cysteinyl LTs, mediate endotoxin-induced mucus production.…”
Section: Discussionmentioning
confidence: 90%
“…20 Other macrolides such as erythromycin have been shown to inhibit hypertrophic and metaplastic changes of goblet cells in rat nasal epithelium, as well as inhibit the proliferation of human mononuclear cells. 21,22 Azithromycin along with clarithromycin are reported to induce apoptosis of activated lymphocytes. 23 In previous studies in our laboratory, azithromycin was also observed to cause reversible autophagy in rabbit tracheal SMCs, but not apoptosis, as well as reversible inhibition of the proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Berger et al [9••] suggest that for glandular subtypes of disease, the use of macrolide antibiotics might represent a reasonable option for targeted therapy. Macrolide antibiotics have been shown to cause marked reduction in mucus hypersecretion in addition to their antibiotic actions [47].…”
Section: Discussionmentioning
confidence: 99%